PENGUASAAN DIRI HAMBA TUHAN DALAM PELAYANAN KAJIAN EKSEGETIKAL 2 TIMOTIUS 4:1-8 - Trisno Kurniadi (Manna Rafflesia, 2017)
Self-mastery is very important for every servant of God, so that a servant of God understands and understands the importance of self-control, because then God's servants will experience changes in life through the process. Self-mastery in question is the ability to hold, curb, and keep oneself from sin so as not to be enslaved by sin. The definition of self-control is the ability to control thoughts, bad habits that are not according to God's will. The Bible records self-control in Galatians 5: 22-23, Proverbs 16:32. Controlling yourself means more than conquerors, and God says in His Word that the servant is the more victorious servant. Based on the presentation of a servant of God must be able to control themselves so as not to be enslaved by sin, so that a servant is called a winner in a competition in service. Therefore it is very important to provide insight into self-control, one of the basic Scriptures that discusses is 2 Timothy 4: 1-8.